Analysis of Automated Text Generation Using Deep Learning - Kumar, Manoj; Kumar, Arnav; Singh, Abhishek; Kumar, Ankit (International Journal For Research In Advanced Computer Science And Engineering, 2021)
A chatbot is a computer program that can converse with humans using artificial intelligence in messaging platforms. The goal of the project is to use and optimize deep learning techniques for making an efficient chat bot. Among current chat bots many are developed using rule-based techniques, simple machine learning algorithms or retrieval-based techniques which doesn’t generate good results.in this paper, we will be comparing performance of three chatbots build by using RNN, GRU and LSTM. These conversation chatbots are mostly used by different businesses, government organizations and non-profit organizations.